Educational migration: factors influencing the attraction of foreign young scientists and the return of Russian young scientists - Filipp D. Belov (RUDN Journal of Economics, 2020)
The article highlights the problem of the emigration of young scientists and students from Russia abroad. The factors affecting the retention of foreign students in the country after graduation are presented, as well as the return of Russian students after receiving higher education abroad. The experience of foreign states in stimulating educational immigration has been analyzed, in particular, scientific programs have been considered to attract foreign students for the purpose of studying in higher education institutions. Similarly, scientific, industrial and economic benefits are singled out in the article with the accumulation of intellectual capital in the country. The options for managing intellectual capital are considered, for example, the idea of creating scientific centers on the basis of coworking as an effective method for attracting and engaging young scientists for achieving high scientific results is proposed.